2020
DOI: 10.1016/j.dsx.2020.04.045
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and glucose homeostasis in pregnancy. What about antenatal corticosteroids?

Abstract: Background and aims: Administration of corticosteroids is common in obstetric practice. In this concise review we queried on the effects of corticosteroids in pregnancies complicated by SARS-CoV-2. Methods: We performed a literature search on PubMed, regarding the use of corticosteroids in patients with SARS-CoV-2 infection, in pregnancies complicated by SARS-CoV-2, as well as their impact on glycemia in pregnant women with or without diabetes. Furthermore, we searched for effects of SARS-CoV-2 and of other co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Betamehasone is a steroid from the group of corticosteroids, it was used in pregnancies complicated by SARS-CoV-2 for its immunosuppressive and anti-in ammatory properties. However, a potential diabetogenic effect was found, in addition to that SARS-CoV-2 and other coronavirus may have effects on glycemia [10].…”
Section: Discussionmentioning
confidence: 99%
“…Betamehasone is a steroid from the group of corticosteroids, it was used in pregnancies complicated by SARS-CoV-2 for its immunosuppressive and anti-in ammatory properties. However, a potential diabetogenic effect was found, in addition to that SARS-CoV-2 and other coronavirus may have effects on glycemia [10].…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids relieve the inflammatory response caused by infection via anti-inflammatory and immunoregulatory effects (141). However, studies have shown conflicting results regarding its clinical effects (142)(143)(144).…”
Section: Treatmentmentioning
confidence: 99%
“…ACE2 receptors are specific binding sites for the entry of COVID‐19 into the cell, 22 hence caution should be exercised in administration of antenatal corticosteroids to pregnant women prone to preterm labor. 23 …”
Section: Pregnancy and Covid‐19mentioning
confidence: 99%